2003
DOI: 10.1002/path.1309
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell micronodules are a common finding in testicular biopsies from men with impaired spermatogenesis and are associated with decreased testosterone/LH ratio

Abstract: To assess the biological significance of Leydig cell 'hyperplasia' in man, Leydig cell distribution, volume, and function were studied in patients with infertility or testicular cancer and in suddenly deceased controls. A total of 156 biopsies from 95 patients and 18 necropsies from 13 controls were examined using a semi-quantitative stereological method. In patients, serum concentrations of testosterone, sex hormone binding globulin (SHBG), luteinizing hormone (LH), follicle stimulating hormone (FSH), oestrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 16 publications
8
82
0
Order By: Relevance
“…In fact, testicular biopsies from infertile men with impaired spermatogenesis showed Leydig cell clusters which have the appearance of Leydig cell hyperplasia. These men have decreased testosterone:LH ratio (Holm et al 2003) and testosterone:oestradiol ratio (Andersson et al 2004). This indicates a role of oestrogen in testes with poor spermatogenesis, although the mechanism is not understood.…”
Section: Testicular Dysgenesis Syndrome and Phthalatesmentioning
confidence: 99%
“…In fact, testicular biopsies from infertile men with impaired spermatogenesis showed Leydig cell clusters which have the appearance of Leydig cell hyperplasia. These men have decreased testosterone:LH ratio (Holm et al 2003) and testosterone:oestradiol ratio (Andersson et al 2004). This indicates a role of oestrogen in testes with poor spermatogenesis, although the mechanism is not understood.…”
Section: Testicular Dysgenesis Syndrome and Phthalatesmentioning
confidence: 99%
“…Surprisingly, the distribution of RCs did not correlate with the severity of androgenic dysfunction in TDS patients with LC micronodules, which was reflected in this study by lower serum testosterone/LH-ratios, decreased serum inhibin B and by reduced testis size, in line with our previous study. 5 In another study, we have demonstrated that LC micronodules in patients with TDS and Klinefelter syndrome, a condition known for very large clusters of LCs, contain proportionally higher numbers of immature LCs due to an increased renewal of the LCs stimulated by LH. 6 The data in the present study provides evidence that the scarcity of RCs may be a characteristic feature of immature adult LCs, this hypothesis being in concert with previous studies of hyperplastic LCs in infertile patients and men with Klinefelter syndrome.…”
Section: Discussionmentioning
confidence: 90%
“…4 The LC micronodules, defined as more than 15 LCs in a cross-section, have previously been associated with a low testosterone/luteinising hormone (LH)-ratio, reflecting an endocrine hypofunction. 4,5 It was recently found that micronodules contain cells at different stages of differentiation with significantly increased proportions of immature LCs within micronodules in patients with germ cell tumours and in patients with Klinefelter syndrome, confirming the importance of stimulation by LH or human chorionic gonadotropin (hCG). 6 Whether the aggregation of LCs is a feature linked to impaired testis development or only represents a post-pubertal compensation for lower androgen levels has not been firmly established.…”
Section: Introductionmentioning
confidence: 95%
“…However, these rats also suffered a significant body weight loss and subsequently also smaller testis weights, which may explain the hampered testosterone secretion. Lowered testosterone levels and Leydig cell hyperplasia are common features among infertile men [58,59] and higher levels of PFOA and PFOS has previously been shown in infertile men [60]. On the other hand, there are also studies showing no adverse PFOA or PFOS-effects on semen parameters in neither men [41] nor rats [42].…”
Section: Discussionmentioning
confidence: 96%